THE GOTHIC ELEMENTS IN TWILIGHT MOVIES: A MODERN INTERPRETATION OF GOTHIC LITERATURE AN ANALYSIS OF LANGUAGE READINESS IN TOURISM SECTOR: A CASE STUDI OF FIVE POPULER DESTINATIONS IN PALEMBANG - Dela Kurnia (English Literature Department, Faculty of Economics, Law, and Humanities, 2025)
Tourism is one of the economic sectors that plays an important role both locally and globally, where effective communication becomes a crucial bridge between hosts and guests. Language readiness is identified as a fundamental factor that determines the quality of tourist experience and destination competitiveness. This study aims to analyze the level of language readiness in five popular tourist destinations in Palembang City: Ampera Bridge, Kemaro Island, Pempek Village, Kuto Besak Fortress, and Sultan Mahmud Badaruddin II Museum. Using a qualitative approach with descriptive case study design, data were collected through structured observations, semi-structured interviews with 11 informants (destination managers, tour guides, traders, and transportation providers), and documentation analysis. The findings reveal significant variations in language readiness levels across destinations, with Sultan Mahmud Badaruddin II Museum demonstrating the highest readiness through QR code audio guides and English information boards, while Pempek Village shows the lowest readiness with limited multilingual infrastructure. Communication barriers identified include limited vocabulary, accent differences, lack of confidence among staff, and absence of formal language training programs. The study concludes that systematic development of language training programs, improvement of multilingual infrastructure, and adoption of assistive technology are essential for enhancing Palembang's tourism competitiveness.